Outcome of Pregnancy Complicated by Threatened Abortion - Dongol, A; Mool, S; Tiwari, P (Kathmandu University Medical Journal, 2012)
Background Threatened abortion is the most common complication in the first half of pregnancy. Most of these pregnancies continue to term with or without treatment. Spontaneous abortion occurs in less than 30% of these women. Threatened abortion had been shown to be associated with increased incidence of antepartum haemorrhage, preterm labour and intra uterine growth retardation. Objective This study was to asses the outcome of threatened abortion following treatment. Methods This prospective study was carried out in Dhulikhel Hospital - Kathmandu University Hospital from January 2009 till May 2010. Total 70 cases of threatened abortion were selected, managed with complete bed rest till 48 hrs of cessation of bleeding, folic acid supplementation, uterine sedative, and hormonal treatment till 28 weeks of gestation. Ultrasonogram was performed for diagnosis and to detect the presence of subchorionic hematoma. Patients were followed up until spontaneous abortion or up to delivery of the fetus. The measures used for the analysis were maternal age, parity, gestational age at the time of presentation, previous abortions, presence of subchorionic hematoma, complete abortion, continuation of pregnancy, antepartum hemorrhage, intrauterine growth retardation and intrauterine death of fetus. Results Out of 70 cases subchorionic haematoma was found in 30 (42.9%) cases. There were 12 (17.1%) patients who spontaneously aborted after diagnosis of threatened abortion during hospital stay, 5 (7.1%) aborted on subsequent visits while 53 (75.8%) continued pregnancy till term. Among those who continued pregnancy intrauterine growth retardation was seen in 7 (13.2%), antepartum hemorrhage in 4 (7.5%), preterm premature rupture of membrane in 3 (5.66%) and IUD in 3 (5.66%). Spontaneous abortion was found more in cases with subchorionic hematoma of size more than 20 cm2. Conclusion In cases of threatened abortion with or without the presence of subchorionic hematoma, prognostic outcome is better following treatment with bed rest, uterine sedatives, folic acid supplementation and hormonal treatment. http://dx.doi.org/10.3126/kumj.v9i1.6261 Kathmandu Univ Med J 2011;9(1):41-4